2018
DOI: 10.1370/afm.2202
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and Socioeconomic Deprivation in Primary Care Consultations

Abstract: PURPOSEThe influence of multimorbidity on the clinical encounter is poorly understood, especially in areas of high socioeconomic deprivation where burdensome multimorbidity is concentrated. The aim of the current study was to examine the effect of multimorbidity on general practice consultations, in areas of high and low deprivation. METHODSWe conducted secondary analyses of 659 video-recorded routine consultations involving 25 general practitioners (GPs) in deprived areas and 22 in affluent areas of Scotland.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 23 publications
3
50
0
Order By: Relevance
“…[7][8][9] Although affluent patients with multimorbidity get 25% longer consultations, similar patients in deprived areas get no additional time. 10 The consequences are unmet need, poorly coordinated care, and greater reliance on unscheduled care services -modern manifestations of the inverse care law.…”
Section: Improved Effectiveness Of Care But Variable Deliverymentioning
confidence: 99%
“…[7][8][9] Although affluent patients with multimorbidity get 25% longer consultations, similar patients in deprived areas get no additional time. 10 The consequences are unmet need, poorly coordinated care, and greater reliance on unscheduled care services -modern manifestations of the inverse care law.…”
Section: Improved Effectiveness Of Care But Variable Deliverymentioning
confidence: 99%
“…The lower uptake of eligible patients with elevated cholesterol was also due to purposeful recruitment in areas of low deprivation (4/6 practices). It is recognised that patients from these deprived UK areas may face greater challenges in engaging with preventive and primary health care in the context of multiple morbidities and competing health and other life priorities [26].…”
Section: Limitationsmentioning
confidence: 99%
“…Despite these recommendations, research in Scotland has shown that the greater need of patients with multimorbidity living in the most deprived quarter of areas is not reflected in longer consultation length. This is in contrast to the least deprived quarter of areas where those with multimorbidity received longer consultations than those without (14). This is an example of the inverse care law, where the availability of good medical care tends to vary inversely with need.…”
Section: Introductionmentioning
confidence: 94%
“…Deprivation was based on the patient's area of residence (Lower Super Output Area level) using deciles of the 2015 Index of Multiple Deprivation (14), grouped into high deprivation (deciles 1-3), medium deprivation (4-7) or low deprivation (8)(9)(10). Linkage was undertaken by CPRD.…”
Section: Socioeconomic Deprivationmentioning
confidence: 99%